El análisis geoespacial en el estudio de la movilidad y el transporte en una Universidad Pública Mexicana - Guerra Hernández, Miriam Anahí (2023)
The link between sustainability and universities brought with it the mainstreaming of that perspective as an institutional agenda, with application to different areas of university life. In the Latin-American context, one of the most relevant problems of urban spaces is the lack of comprehensiveness in mobility policies, coupled with the socio-spatial and residential fragmentation a situation that affects in a differentiated manner the diverse inhabitant collectives including the university community. The objective of this paper is to present the contributions of geospatial analysis using QGis software, for the analysis of daily mobility in the university community of a Higher Education Institution (HEI) in México, emphasizing the social dimension of mobility. The approach was conducted in two phases: 1) Through bibliographical and documentation review on the state of mobility in the University Centre under study and 2) A geospatial analysis from the data obtained through a survey and field observation. The main findings indicate that geospatial analysis is a tool that contributes to the application of sustainability in integral terms in favor of university community mobilities.